2017
DOI: 10.1080/14767058.2017.1334046
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body mass index and oxytocin exposure in nulliparous women: is there an interaction associated with maternal and neonatal morbidities?

Abstract: BMI and oxytocin dosage are associated with select maternal and neonatal outcomes. However, the lack of interaction between BMI and oxytocin product suggests that the higher administered dose of oxytocin associated with increasing BMI does not synergistically potentiate maternal and neonatal morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…During delivery, sterile operations should be strictly performed, the digital anal examination is strictly forbidden, 14 the frequency of vaginal examination should be reduced as far as possible to reduce the incidence rate of retrograde infection, 15 indications of cesarean section and lateral episiotomy should be strictly grasped, antibacterial drugs can be used for a short time for those undergoing cesarean section to prevent the infection, and the maternal management should be strengthened 16 to improve the hospital delivery rate, 17 prevent postpartum hemorrhage, 18 and reduce the injury of birth canal due to delivery as far as possible. 19 During puerperium, it is recommended that puerperae get enough sleep, strengthen nutrition reasonably, and improve the body's immunity, the health management be strengthened, and prevention measures be actively taken for puerperae with high-risk factors, thereby improving the prognosis of patients and reducing the incidence of puerperal infection. 20 The limitation in our study still exists that a relatively larger study population from different regions requires to be included to confirm our finding and even reflect data at national level, which may provide fundamental leads for the diagnosis and treatment of puerperal infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During delivery, sterile operations should be strictly performed, the digital anal examination is strictly forbidden, 14 the frequency of vaginal examination should be reduced as far as possible to reduce the incidence rate of retrograde infection, 15 indications of cesarean section and lateral episiotomy should be strictly grasped, antibacterial drugs can be used for a short time for those undergoing cesarean section to prevent the infection, and the maternal management should be strengthened 16 to improve the hospital delivery rate, 17 prevent postpartum hemorrhage, 18 and reduce the injury of birth canal due to delivery as far as possible. 19 During puerperium, it is recommended that puerperae get enough sleep, strengthen nutrition reasonably, and improve the body's immunity, the health management be strengthened, and prevention measures be actively taken for puerperae with high-risk factors, thereby improving the prognosis of patients and reducing the incidence of puerperal infection. 20 The limitation in our study still exists that a relatively larger study population from different regions requires to be included to confirm our finding and even reflect data at national level, which may provide fundamental leads for the diagnosis and treatment of puerperal infection.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, it is suggested that early pregnancy be determined in time, health management during pregnancy be actively implemented, the standard maternal manual be created before 13 weeks of gestation, the comprehensive physical examination be given, and high‐risk pregnancy and pathologic pregnancy be screened to improve the safety of pregnancy. During delivery, sterile operations should be strictly performed, the digital anal examination is strictly forbidden, the frequency of vaginal examination should be reduced as far as possible to reduce the incidence rate of retrograde infection, indications of cesarean section and lateral episiotomy should be strictly grasped, antibacterial drugs can be used for a short time for those undergoing cesarean section to prevent the infection, and the maternal management should be strengthened to improve the hospital delivery rate, prevent postpartum hemorrhage, and reduce the injury of birth canal due to delivery as far as possible . During puerperium, it is recommended that puerperae get enough sleep, strengthen nutrition reasonably, and improve the body's immunity, the health management be strengthened, and prevention measures be actively taken for puerperae with high‐risk factors, thereby improving the prognosis of patients and reducing the incidence of puerperal infection .…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the US have shown that women with increasing BMI seem to receive both higher cumulative oxytocin doses and higher oxytocin infusion rates in augmentation and induction of labor. [159][160][161][162][163][164] Deliveries among women with class III obesity with induced and spontaneous labors have shown a higher maximum rate of oxytocin compared with normal weight women. 163 Furthermore, women with obesity class II, with spontaneous start of labor, required higher amounts of oxytocin during the first three hours after labor arrest had been diagnosed compared with lower BMI groups.…”
Section: In Overweight and Obesitymentioning
confidence: 99%